2023
DOI: 10.1007/s00404-022-06900-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of copy number variation sequencing in fetuses with increased nuchal translucency: a retrospective study

Abstract: To assess the clinical application value of copy number variation sequencing (CNV-seq) combined with karyotype analysis in prenatal diagnosis of fetuses with increased nuchal translucency. Methods 205 fetuses who were diagnosed with increased nuchal translucency (NT ≥ 2.5 mm) by ultrasound between gestational ages of 11 and 13 + 6 weeks from June 2017 to December 2020 in Tongji Hospital were enrolled. Amniotic uid samples were extracted for performing karyotype analysis and CNV-seq after patient's written info… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Previous research revealed that NT thickness was positively associated with the detection rates of genetic aberrations [13]. Meanwhile, although the cut-off value of NT thickness was 3.0mm or above the 99 th percentile of crown-rump length according to the American College of Obstetricians and Gynecologists (ACMG) and Society for Maternal Fetal Medicine, previously reports indicated that NT thickness larger than 2.5mm was associated with an increased risk of genetic aberrations [13,14]. So, chromosomal aberrations in fetuses with different NT thicknesses were investigated in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research revealed that NT thickness was positively associated with the detection rates of genetic aberrations [13]. Meanwhile, although the cut-off value of NT thickness was 3.0mm or above the 99 th percentile of crown-rump length according to the American College of Obstetricians and Gynecologists (ACMG) and Society for Maternal Fetal Medicine, previously reports indicated that NT thickness larger than 2.5mm was associated with an increased risk of genetic aberrations [13,14]. So, chromosomal aberrations in fetuses with different NT thicknesses were investigated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In fetuses with choroid plexus cysts, nasal bone hypoplasia and ventriculomegaly, the detection rates of chromosome abnormalities were 7.5% [7], 5.9%-17.8% [8-10] and 6.8% [11], respectively. In fetuses with increased NT thickness, the detection rates of chromosome abnormalities ranged from 19.4-23.7% [12][13][14]. In addition to abnormal karyotypes, pathogenic/likely pathogenic copy number variations (P/LP CNVs) were found to be associated with ultrasound soft markers via chromosomal microarray analysis (CMA) and copy number variation sequencing (CNV-seq) [15].…”
Section: Introductionmentioning
confidence: 99%